2010
DOI: 10.1111/j.1755-9294.2010.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ki67 and modified AgNOR in dysplastic epithelial lesion, primary squamous cell carcinoma and metastatic squamous cell carcinoma of head and neck

Abstract: The variations in nucleolar organizer regions (AgNOR) and the increase in Ki67 expression and correlation with histological findings in 64 specimen squamous epithelium from normal epithelium to overt carcinoma were evaluated. Mean AgNOR counts (mAgNOR), proliferative index (pAgNOR), variation in size and dispersion of AgNOR dots in cells were graded and compared in normal, dysplastic, primary and metastatic squamous cell carcinoma (SCC). The Ki67 percentage is significantly increased from normal squamous to SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The variation observed in many cases in this study is reported in studies in dogs that evaluate the AgNOR count in cutaneous SCCs, where there is no well‐established association between the count of NORs and the histological grading 11,12 . In humans, a gradual increase in the AgNOR index is described in head and neck SCCs as the tumour becomes poorly differentiated 9,10 …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The variation observed in many cases in this study is reported in studies in dogs that evaluate the AgNOR count in cutaneous SCCs, where there is no well‐established association between the count of NORs and the histological grading 11,12 . In humans, a gradual increase in the AgNOR index is described in head and neck SCCs as the tumour becomes poorly differentiated 9,10 …”
Section: Discussionmentioning
confidence: 72%
“…Certain morphological characteristics, such as the p16, have been identified to have an association with the likelihood of metastasis, hold prognostic significance, and may impact treatment decisions as well as survival for SCCs in humans 6,7 and cats 8 . The AgNOR index is a marker of cellular activation of tumour cells, which reflects the active activity of SCC tumour cells, further aiding in the identification of cell proliferation in both humans 9,10 and animals 11,12 . In the same way, the distinction of an individual epithelial neoplastic cell, and especially those that acquire a fusiform shape, due to the epithelial–mesenchymal transition during the dedifferentiation stage, has become extremely important in humans 13 .…”
Section: Introductionmentioning
confidence: 99%
“…As the transition of normal oral epithelium to dysplasia to carcinoma is characterized by increased cell proliferation, Ki-67 which is a gold standard proliferative index, has been extensively examined in oral dysplasia and OSCC with increased expression in higher grades of dysplasia. [6][7][8] The objective of this study was to study the pattern of staining and Labelling Index (LI) of expression of p53 protein and Ki-67 antigen in oral premalignant lesion and OSCC and to find out the relationship between Labelling Index of p53 protein and Ki-67 antigen in oral premalignant lesion and OSCC.…”
Section: Introductionmentioning
confidence: 99%